Effects of a professional development program on teachers' oral corrective feedback practices. (November 2022) - Ha, Xuan Van
Abstract: The roles and patterns of oral corrective feedback in L2 classrooms have received extensive research attention; however, whether teachers' feedback practices can be changed via professional development activities remains to be shown. This study represents the first documented attempt to investigate the impact of a professional development program on EFL teachers' actual feedback practices. The program comprised a workshop facilitating the teachers to discuss recent research findings regarding oral corrective feedback and a follow-up program of experiential learning through reflective practice for eight weeks. The data included 30 h of video-recordings of classroom observations with ten experienced teachers before and after the program. The findings revealed that the teachers changed their practices significantly regarding four aspects of feedback, namely, feedback frequency, types, targets, and feedback for fluency work. These changes were regarded as positive because they were aligned with the implications of research findings. Implications for in-service teachers' professional development are discussed. Highlights: Teachers' uptake of workshop is boosted by opportunities for experiential learning. The targeted PD program has a significant impact on teachers' feedback practices. PD program creates spaces for teachers to exercise professional learning autonomy. There is a rise in CF frequency and more balanced use of three broad CF categories. Teachers' changes in CF use are aligned with the implications of research findings.